Mix design procedure for foamed asphalt mixtures. Issue 4 (1st October 2016) - Yin, Fan; Arámbula-Mercado, Edith; Newcomb, David
Abstract : Mechanical foaming is the most popular method for producing warm mix asphalt in the United States; yet, a standard mix design procedure for foamed asphalt mixtures has not been established. Currently, the design of foamed asphalt mixtures consists of determining the optimum binder content by following a standard hot mix asphalt (HMA) design procedure and then estimating the foaming water content based on the foamer manufacturer's recommendation, engineering judgement, or previous experience. This practice fails to account for the effect of foaming on binder and mixture properties, and therefore may not ensure desirable foamed mixture performance. To overcome this shortcoming, additions to the standard mix design procedure were proposed in this study in order to accommodate foamed asphalt mixtures, which included optimisation of foaming water content and evaluation of foamed mixture performance. In addition, the proposed procedure was verified using materials procured from two field projects. The optimum foaming water content ( W opt %) was first determined by comparing the workability results of foamed mixtures at various foaming water contents. Afterwards, the foamed mixture at W opt % was tested for coatability and performance evaluation, and all laboratory test parameters complied with established American Association of State Highway and Transportation Officials or agency specifications or were equivalent to or better than the control HMA test results. Therefore, the proposed foamed mix design procedure seemed a viable alternative for designing foamed mixtures with adequate pavement performance.